RANCANG BANGUN SISTEM COURSES ONLINE DENGAN METODE DEVOPS (STUDI KASUS : HELLOCATION) - Damianus Jemmy Aposto; Dani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Writing this thesis discusses Courses Online Hellocation which do not yet have learning media for users to learn and receive learning materials from tutors, as well as the lack of effectiveness of the learning process which cannot be accessed anywhere and anytime. The Courses Online Hellocation application will be made using the devops method, which is the unification of divisions, processes and technology in the software or application development phase. With the aim of creating a website-based application that has an easy-to-understand interface. In order to enhance the user experience, the interface of this application is designed in an intuitive and user-friendly manner. It is intended that users can easily interact with the application and make effective use of its features. In addition, this Online Courses application also provides benefits for all Hellocation learning members.